MiR-4458 inhibits the epithelial–mesenchymal transition of hepatocellular carcinoma cells by suppressing the TGF-β signaling pathway via targeting TGFBR1. (23rd April 2020) - Zhang, Yuke; Shi, Kun; Liu, Hang; Chen, Wei; Luo, Yunhai; Wei, Xufu; Wu, Zhongjun
Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal cancers in the world. MicroRNAs play a pivotal role in the progression of various cancers. To date, very little attention has been paid to miR-4458. Therefore, the aim of our study was to explore the function and underlying molecular mechanism of miR-4458 in HCC. We found that the expression of miR-4458 was reduced in HCC tissues and cell lines. Forced overexpression of miR-4458 inhibited the migration, invasion, and epithelial–mesenchymal transition (EMT) of HCC cells, while downregulation of miR-4458 promoted the aggressive phenotype. Furthermore, transforming growth factor beta receptor 1 (TGFBR1), the modulator of the TGF-β signaling pathway, was verified to be a novel target gene of miR-4458 by dual-luciferase reporter gene assay. Upregulated miR-4458 dramatically abolished TGFBR1 and p-Smad2/3 expression, thus blocking the TGF-β signaling pathway. Moreover, restoration of TGFBR1 partially rescued the miR-4458-mediated suppressive effect on the migration, invasion, and EMT and reactivated the TGF-β signaling pathway in HCC cells. In summary, our findings first demonstrated a mechanism of miR-4458 in HCC cell migration, invasion, and EMT by regulating the TGF-β signaling pathway via directly targeting TGFBR1.